2014
DOI: 10.13102/sociobiology.v61i4.510-516
|View full text |Cite
|
Sign up to set email alerts
|

Pollination Services Provided by Melipona quadrifasciata Lepeletier (Hymenoptera: Meliponini) in Greenhouses with Solanum lycopersicum L. (Solanaceae)

Abstract: Stingless bees are considered particularly promising for use as commercial pollinators. However, studies testing the effectiveness of these bees in pollinating grape tomatoes in greenhouses are not yet available. This work aimed to analyze the floral biology of the grape tomato and evaluate whether the additional pollination performed by Melipona quadrifasciata Lepeletier generates an effective increase in production and improves the quality of this variety of tomato when grown in greenhouses. The research too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…The use of rational breeding techniques, knowledge of the explored flora, the implementation of management techniques, and artificial feeding have allowed the expansion of meliponiculture (Jaffé et al 2015). Many species are popular and are raised to obtain products which generate jobs and income and, at the same time, maintain biodiversity (Kerr et al 2001;Imperatriz-Fonseca and Nunes-Silva 2010;Contrera et al 2011;Ollerton et al 2011;Freitas and Nunes-Silva 2012;Bartelli and Nogueira-Ferreira 2014). In Brazil, many tree species and agricultural crops are pollinated by these bees and their effective pollination performance has been confirmed for more than 30 different agricultural crops (Heard 1999;Slaa et al 2006;Castro et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The use of rational breeding techniques, knowledge of the explored flora, the implementation of management techniques, and artificial feeding have allowed the expansion of meliponiculture (Jaffé et al 2015). Many species are popular and are raised to obtain products which generate jobs and income and, at the same time, maintain biodiversity (Kerr et al 2001;Imperatriz-Fonseca and Nunes-Silva 2010;Contrera et al 2011;Ollerton et al 2011;Freitas and Nunes-Silva 2012;Bartelli and Nogueira-Ferreira 2014). In Brazil, many tree species and agricultural crops are pollinated by these bees and their effective pollination performance has been confirmed for more than 30 different agricultural crops (Heard 1999;Slaa et al 2006;Castro et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…fasciata was the most abundant. Other species of the genus Melipona have been previously reported as efficient pollinators of Solanaceous crops such as tomato and eggplant (Bartelli and Nogueira-Ferreira, 2014;Nunes-Silva et al, 2013). A study assessing the effects of imidacloprid consumption in bumble bees pollinating tomatoes showed that imidacloprid affected the probability of performing sonication behavior in flowers (Switzer and Combes, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sarang lebah tak bersengat ini kadang berasosiasi antara pohon, rayap, tawon atau semut (Roubik , 2006). Lebah ini tidak memiliki sengat fungsional, mudah ditangani karena tidak menyengat dan sebagian kurang agresif, dengan jumlah anggota koloni yang padat, dan sarang bersifat perennial dan mengumpulkan makanan dalam jumlah besar (Bartelli & Nogueira-Ferreira, 2014). Di Indonesia Lebah ini memiliki beberapa nama daerah, yaitu Kelulut (Kalimantan), Galo-galo (Sumatera), Klanceng/Lenceng (Jawa), dan Te'uweul (Sunda) (Erniwati;2013) Hasil penelitian menunjukkan bahwa sarang lebah Trigona sp.…”
Section: Pendahuluanunclassified